Elaboration De La Carte Géotechnique De La Ville De Lubumbashi Guide Technique De Sélection Des Sites D’implantation D’ouvrages Du Génie Civil - Portance, Kasongo wa Mutombo; Gustave, Mukoko Kalenda; Louis, Kipata Mwabanwa; Marie, Lunda Ilunga Jean (European Scientific Journal, ESJ, 2018)
Geotechnical data processing that ignores the spatial aspect leads to loss of information, specification errors, non-convergent and ineffective estimation, and prediction errors. These data often present a spatial dependence (problem of spatial autocorrelation) and a heterogeneity in space (clustering problem) and sometimes temporal. The geotechnical mapping of Lubumbashi soils based on 1672 observations according to the AASHTO classification system (designation ASTM D-3282 M145), divided these soils into 11 subgroups: A-1-a (sandy gravels with clays), A-1-b (gravelly sands with clays), A-2-4 (gravelly sands with silts), A-2-5 (sandy gravels plastic silts), A-2-6 (gravelly sands with clays), A-2-7 (gravelly sands with active clays), A-4 (silts with sands), A-5 (plastic silts with sands), A-6 (clays with sand), A-7-5 (active clays), A-7-6 (active clays). Class A-3 has not been identified. Soils with an index 5 contain clays of the illite type whereas the others consist of kaolinites on plasticity Casagrande chart. Class A-1 and A-2 are good for foundation engeneering and form the potential aquifers of the city (groundwater, drainage zone, groundwater recharge zone). They also constitute favorable sites for the implantation of the cimeteries (aerated soils) because the time necessary for the destruction of bodies is brief. In this case the rotation of 5 years can be used without problem for a city with dense population like the city of Lubumbashi. Soils A-4 and A-5 are also good for subgrade-foundations, but are highly vulnerable to erosion and liquefaction. Soils A-6 and A-7 form impervious bedrock substrates. These sites can be used as the landfill site. They are also considered clay deposits in the manufacture of ceramics and refractory products. Taking into account the nature of the source rocks, the same lithology can give several types of soils depending on the parameters influencing weathering: climate (Lubumbashi’s tropical climate), pH, Eh, topography, anthropization, etc. One type of soil may also come from several rock formations. The geotechnical map developed compared to the geological map of Lubumbashi, shows that soils A-1 and A2 come from conglomerates, sandstones and the lateritization process of rock formations very rich in iron such as dolomitic shale and shale. Soils A-4 and A-5 are often alteration products of silty shales and siltstones, while soils A-6 and A-7 are derived from the alteration of clay and dolomitic rocks: shales, dolomitic shales, silty shales, limestones and dolomites. The geological map is fondamental but not sufficient document for geotechnical studies. A detailed study of the soils and the state of weathering of the different parts of a rock mass is inevitable.